Dampness on residential college in Universiti Teknologi Mara (UiTM) Shah Alam / Nur Farawahida Rosli - Rosli, Nur Farawahida (Faculty of Architecture, Planning and Surveying, 2013)
Dampness can be described as an excessive quantity of moisture contained within building materials and components which cause adverse movements and deterioration of the facade or structure of the building. The purpose of this research to study the dampness, identify the agents contributing towards dampness on residential college in UiTM Shah Alam and to recommend the remedial action of the dampness. The methods which used to collect the data and information of this research are distribution questionnaire, semi-structure interview and the site observation. The selected case study for this research is College Teratai because this residential college is old residential college compare the others residential college in UiTM Shah Alam. Based on the site observation, the location which possibility for influence the dampness is toilet because nearest with sources of moisture. The significant of study will carry out the remedial action to solve these problem and it can be applied in the future for minimize these problem of dampness on residential college. The result show the mostly agents contributing towards dampness on residential college in UiTM Shah Alam is excess moisture such as penetrating damp and rising damp.